The immune response of rabbits immunized by Salmonella typhimurium and Lactobacillus acidophilus - Al-Samarraae, Ikram A. A.; A. Kareem, Alaa (The Iraqi Journal of Veterinary Medicine, 2018)
Antigens prepared from sonicated Salmonella typhimurium (KWCSA-ST) and Lactobacillus acidophilus (KWCSA-LBA) were used to evaluate synergistic effect on interlukine production (IL-2, IL-4) and Immunoglobulin-G (IgG) which were evaluated by using Enzyme Linked Immunosorbent Assay and Delayed Type Hypersensitivity-skin test at day 20 post immunization. Twenty five rabbits of both sexes, 2-3 Kg body weight, were divided into five equal groups; the first group immunized by KWCSA-ST (1000 µg/ml) and KWCSA-LBA (1000 µg/ml), the second group by KWCSA-ST (1000 µg/ml) and KWCSA-LBA (500 µg/ml), the third group by KWCSA-ST (1000 µg/ml) as positive control, the fourth group by KWCSA-LBA (1000 µg/ml) as positive control and the fifth group was injected by P.B.S. (pH7.2) as negative control group subcutaneously. The result of delayed type hypersensitivity showed an increase in the means of erythema and induration in the 1st group after 24hrs and 48hrs while the 4th group recorded the lowest mean after 24hrs and 48hrs. These means showed significant differences (P˂0.05) compared with injection by 1:2 and 1:4 diluted Ag. While the results of IgG showed that the highest concentration was at 35th day in the first group while the lowest concentration at 35th day in the fourth group with significant differences (P<0.05). Also the high concentration of IL-2, IL-4 was recorded in the first group at 35th day and the lowest concentration was in the fourth group at 35th day with significant differences (P<0.05); also the results showed significant differences (P<0.05) between the 1st, 2nd, 3rd compared with 4th and 5th groups.